EMPOWERING THE READING READABILITY - Handoko, Handoko (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
A general assumption about reading is that students improve their reading ability by reading a lot. This research was conducted to explain the use of extensive reading and aimed to figure out its implementation in improving students’ reading readability by using the class action research technique. The data of this research relates to the students ‘reading progress shown in their reading reports: spoken and written summary, reading comprehension and vocabulary mastery and their participation. The strategy was evolved in the continuity of reading. Students were encouraged to read extensively in and outside class. The findings indicated that the implementation could improve students’ reading readability.This attainment demonstrated that students’ reading readabilityis frosted through the continuity of reading. Other facts showed that students enjoyed reading. Students’ curiosity was also a significant factor. Their high curiosity explained why students continued reading though they realized that materials they read were difficult enough. Students’ self-confidence was also built as they were required to write a retelling story and to share their previous reading. Instead of their retelling and summarizing, students felt to be appreciated as readers. This appreciation indirectly helped students to improve the reading fondness.